PENGELOLAAN PEMBELAJARAN PENDIDIKAN ANAK USIA DINI (PAUD) DI KELOMPOK BERMAIN - Nurhasanah, Nurhasanah (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The purpose of this study is to explain (1) planning PAUD learning in Playgroups (Kb) Mulia Kasih PAUD, (2) implementing learning, and (3) Assessment of learning. The type of research used is qualitative research. The research was conducted at Mulia Kasih PAUD Mulia Kasih. The data collection techniques in this study were interviews, observation, and documentation. The results of this study are (1) ECD syllabus is outlined in the form of semester planning, weekly planning and daily / meeting planning (2) Implementation of learning in Smart KB begins with (a) happy morning, (b) habituation activities, (c) transition , (d) environmental footing, (e) footing before playing, (f) footing during play, (g) footing after playing, (h) introduction to prayer, (i) closing. The learning process uses the method of playing while learning through center class learning with the Beyond Center and Circle Time approach and the question and answer method, stories, role playing or direct field practice. In a comfortable, safe, clean and healthy playing atmosphere. (3) Assessment of learning in Smart KB is done by observation at all.